The effect of the Irish smoke-free workplace legislation on smoking among bar workers - ALLWRIGHT, SHANE; PAUL, GILLIAN MARGARET (My University, 2009)
Background: On 29 March 2004, the Republic of Ireland (ROI) became the first EU country to introduce a nationwide ban on workplace smoking. While the focus of this measure was to protect worker health by reducing exposure to second-hand smoke, other effects such as a greater reduction in smoking prevalence and consumption were likely among bar workers. Methods: A random sample of bar workers from Cork city were surveyed before (n = 129) and after (n = 107; 82.9% follow-up rate) implementation of the smoke-free legislation. Self report and combined self report and cotinine concentration were used to determine smoking status. For comparison a cross-sectional random telephone survey of the general population (ROI) was conducted before and 1 year after the smoke-free legislation. There were 1240 pre- and 1221 participants post-ban in the equivalent age and occupational subset of the general population. Results: There was a non-significant decline in smoking prevalence among bar workers 1 year post-ban (self report: ?2.8% from 51.4% to 48.6%, P = 0.51; combined self report and cotinine: ?4.7% from 56.1% to 51.4%, P = 0.13), but a significant decline in consumption of four cigarettes (95% CI 2.21?6.36) per day. Within the occupationally equivalent general population sub-sample there was a significant drop (3.5%, P = 0.06) in smoking prevalence but no significant change in consumption. Conclusions: Ireland's smoke-free workplace legislation was accompanied by a drop in smoking prevalence in both bar workers and the general population sub-sample.
PUBLISHED
Keywords: Public Health; Tobacco